Collection Inventory in a Canadian Academic Dentistry Library. - Buda, Maria; He, Helen (Journal of the Canadian Health Libraries Association (JCHLA), 2012)
Introduction: Collection inventories are time consuming but necessary to clean up catalogue records and improve access and retrieval. This article outlines the methods of carrying out an inventory project at the Dentistry Library, University of Toronto, for the first time in 16 years. As a result, a kit was developed to help implement this project in future years. Description: The kit outlines the steps for the inventory including creating a shelf-list using SIRSIDynix Symphony 3.0's report function, importing into Excel, and separating the collection in smaller sections to make the process less onerous. Outcomes: Readers are informed of the results of this inventory and challenges that arose with the hope that similar projects will be encouraged in other libraries. Collection analysis was not completed in depth, but general conclusions can be stated about the strengths and weaknesses at this time. Discussion: Because of the length of time since the last inventory was completed, this project took longer than expected. The inventory kit, developed from the lessons learned, will facilitate future inventories at the Dentistry Library, as well as other libraries undertaking a collection inventory. Conclusion: Overall, this was a great learning exercise for the Dentistry Library team, and it resulted in improved access to materials by providing users with the correct item information.